PENGARUH DOSIS PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL DUA VARIETAS KACANG HIJAU (Vigna radiata L.) - Nur lela (Jurnal Floratek, 2023)
Efforts to increase green bean production include improving the cultivation system, namely the use of appropriate doses of NPK fertilizer and the use of superior varieties. This study aims to determine the effect of NPK fertilizer doses on the growth and yield of two green bean varieties. This research was conducted at the Experimental Garden II in the eastern sector and the Laboratory of Seed Science and Technology, Faculty of Agriculture, Syiah Kuala Darussalam University, Banda Aceh. The research was carried out from June to August 2022. The materials used in this study were 10 kg volume polybags, 10.8 grams of mung bean seeds of the local variety Gayo lues and the superior variety Evania, rope, paper labels. , stationery, 1.125 kg of Mutiara NPK fertilizer, 225 kg of manure, and 675 kg of Entisol soil, the insecticides used were furadan and Decis with a solution concentration of 2 cc L-1 water. The tools used in this study were hoes, machetes, tape measure, analytical scales, shovels, sieves, gembor, handsprayer, calipers, tape measure, name pamphlets, cameras, and others that support the research process. This study used a 5x2 factorial complete randomized design with 3 replications so that there were 30 experimental units, each experiment consisting of 3 polybags so that there were 90 experimental units. The factors studied were NPK fertilizer doses and green bean varieties. The dosage factor for Mutiara NPK fertilizer consisted of five levels, namely 400, 450, 500, 550 and 600 kg ha-1, the green bean variety factor consisted of 2 levels, namely the local Gayo Lues variety and the Evania variety. The variables observed included plant height, number of productive branches at 50 HST, number of fruitful pods per plant, number of empty pods per plant, pod weight per plant, seed weight per plant and weight of 100 dry seeds. The results showed that the dose of NPK fertilizer had a significant effect on the number of productive branches at 50 HST and the number of pods per plant. Better plant growth and yields were found in the treatment of NPK fertilizer doses of 550 kg ha-1. Furthermore, the variety of mung bean plants had a very significant effect on the number of pods per plant, had a significant effect on plant height at 45 DAP and seed weight per plant. The best plant growth and yields were found in the Evania variety. There is no significant interaction with all observed variables.Keywords: Green beans, NPK fertilizer dosage, variety